Energy Resources and Systems Volume 2: Renewable Resources - Ghosh, Tushar K. (Springer Netherlands : Imprint: Springer, 2011)
This second volume of Energy Resources and Systems is focused on renewable energy resources. Renewable energy mainly comes from wind, solar, hydropower, geothermal, ocean, bioenergy, ethanol and hydrogen. Each of these energy resources is important and growing. For example, high-head hydroelectric energy is a well established energy resource and already contributes about 20% of the world’s electricity. Some countries have significant high-head resources and produce the bulk of their electrical power by this method. However, the bulk of the world’s high-head hydroelectric resources have not been exploited, particularly by the underdeveloped countries. Low-head hydroelectric is unexploited and has the potential to be a growth area. Wind energy is the fastest growing of the renewable energy resources for the electricity generation. Solar energy is a popular renewable energy resource. Geothermal energy is viable near volcanic areas. Bioenergy and ethanol have grown in recent years primarily due to changes in public policy meant to encourage its usage. Energy policies stimulated the growth of ethanol, for example, with the unintended side effect of rise in food prices. Hydrogen has been pushed as a transportation fuel.